2011
DOI: 10.1002/aic.12480
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanic modeling and analysis of the flow regimes in horizontal pneumatic conveying

Abstract: Pneumatic conveying is an important technology for industries to transport bulk materials from one location to another. Different flow regimes have been observed in such transportation processes, but the underlying fundamentals are not clear. This article presents a three-dimensional (3-D) numerical study of horizontal pneumatic conveying by a combined approach of discrete element model for particles and computational fluid dynamics for gas. This particle scale, micromechanic approach is verified by comparing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 76 publications
1
24
0
Order By: Relevance
“…ese phenomena are similar to the observations reported in the experimental work of Wypych and Yi [42] and the simulation study by Kuang and Yu [43]. Figure 14 shows the distribution of time-averaged solids concentration and porosity when a dune passes through the stepped section.…”
Section: Mechanisms Governing Solid Dune/pressure Surge Phenomenasupporting
confidence: 84%
“…ese phenomena are similar to the observations reported in the experimental work of Wypych and Yi [42] and the simulation study by Kuang and Yu [43]. Figure 14 shows the distribution of time-averaged solids concentration and porosity when a dune passes through the stepped section.…”
Section: Mechanisms Governing Solid Dune/pressure Surge Phenomenasupporting
confidence: 84%
“…τ and ε f are the fluid viscous stress tensor and porosity, respectively, which are given as τ=μnormale[(u)+(u)1] and εnormalf=1(i=1kVVi)/ΔV, where V i is the volume of particle i (or part of the volume if the particle is not fully in the CFD cell), k V is the number of particles in the CFD cell, and μ e the fluid effective viscosity determined by k ‐ ε turbulent model, which has been used in our previous work . Note that the effect of gas turbulence on solid flow has been tested, and it is found that the effect can be ignored for coarse particles . However, further tests are needed to justify if this treatment can be applied to fine particles.…”
Section: Model Descriptionmentioning
confidence: 99%
“…The model could then successfully reproduce various flow patterns. Kuang and Yu [19] could predict the various flow regimes in 3D horizontal pneumatic conveying. However, they did not consider gas phase turbulence alteration due to the presence of the dispersed phase.…”
Section: Introductionmentioning
confidence: 99%